PENGARUH WORK LIFE BALANCE DAN WORK ENGAGEMENT TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA KARYAWAN: (Studi Pada PT Sumber Kurnia Alam Bandar Lampung) - Dunan, Hendri; Paolo, Clarissa Chandra (Media Mahardhika, 2025)
Knowing whether work balance and involvement affect employee performance through job satisfaction at PT Sumber Kurnia Alam Bandar Lampung, this research was conducted. This type of research is quantitative and there are 40 questionnaires filled out by employees of PT Sumber Kurnia Alam Bandar Lampung office. Data analysis through path analysis and applying SEM through PLS 4.0 software. Based on the findings, work balance has a negative and moderate effect on employee performance, work involvement has a positive and moderate effect, work balance has a positive and significant effect on job satisfaction, as well as work involvement, job satisfaction has a significant and positive effect on employee performance, work balance variables on performance have a significant indirect effect on job satisfaction, and work involvement variables do not have a mediating effect but, have a direct effect on employee performance.